Light controlled frequency reconfigurable antenna for wireless applications - Reji, V.; Manimegalai, C. T. (International journal of microwave and wireless technologies, 2023)
In this paper, a light-controlled frequency reconfigurable antenna is presented for 5 G, WLAN, and radio altimeter applications. The given (44 × 28) mm2 antenna consists of a radiating V-shaped structure and three stub arrangements. The main λ/2 length stub is used to feed the antenna and the two λ/4, λ/8 length open-circuited stubs are located perpendicular to the main feeding stub for tuning the frequency of the antenna. The length of the stubs can be adjusted by placing (4 × 1.2) mm photodiode switches on the perpendicular stubs. Four experiments are carried out to analyze the performance of the antenna. When light and DC bias voltage is not applied (Experiment-1) to the photodiodes the proposed antenna radiates from 4.1 to 4.63 GHz with 12% bandwidth. When light is applied to the photodiode without DC bias voltage and DC bias voltage is applied without light (Experiment-2,3) the antenna reconfigures its frequency band from 3.43 to 3.6GHz and 4.8 to 5.4 GHz with 4.85% and 12% bandwidth respectively. The antenna shifts the radiation from 4.8 to 5.5 GHz with 14% bandwidth when the light and DC bias voltage is applied to the antenna(Experiment-4). The measured gain of the proposed antenna is greater than 3.8dBi in all the experiments.